Optimisation of the hatchery production of ballan wrasse (Labrus bergylta) with an emphasis on nutritional and environmental requirements - Cavrois-Rogacki, Thomas (Aquaculture, 2019)
Ballan wrasse (Labrus bergylta), successfully used as a biological delouser of Atlantic salmon (Salmo salar), are eco-friendlier alternative to the use of chemotherapeutants. However, the use of wild caught specimens, which account for most of the deployed fish, is not sustainable. Therefore, the industry wishes to transition to farmed ballan wrasse, seen as a more sustainable, reliable and predictable source. However, the hatcheries are facing production challenges common to any new marine fish species including low survival, suboptimal growth, poor feed efficiency and lack of robustness that hampers the up-scaling of the production. To increase hatchery productivity, this doctoral project investigated the nutritional and environmental requirements of the species to develop commercial protocols. The first two experimental chapters focused on live feed (e.g. Artemia) enrichment for ballan wrasse larvae especially for phospholipids and essential fatty acids (chapter II) and selenium (chapter III). Chapter II proposes an effective, simple and easy method for simultaneously boosting the phospholipid and essential fatty acids content of the nauplii. In chapter III, an enrichment protocol was created allowing the hatcheries to target specific selenium contents in their nauplii. Then, research looked at the impact of three temperatures (10, 13 and 16 °C) on juveniles feed intake, growth and digestibility (chapter IV). Results showed that growth performances and feed efficiency were greatly improved at 16 °C compared to the lower temperatures. If implemented commercially, this could shorten the on-growing nursery phase by more than four months. Chapter V then studied the effects of dietary protein content (standard 51% vs. high 59 % crude protein) and protein source (fish meal vs plant-based) on the growth performances, feed efficiency and digestibility of juveniles reared at 15 °C. The study showed the successful substitution of fish meal by soy protein concentrate and pea protein, without compromising growth nor fish ...